Response to antiviral therapy in haematopoietic stem cell transplant recipients with cytomegalovirus (CMV) reactivation according to the donor CMV serological status. (March 2016) - Servais, S.; Dumontier, N.; Biard, L.; Schnepf, N.; Resche-Rigon, M.; Peffault de Latour, R.; Scieux, C.; Robin, M.; Meunier, M.; Xhaard, A.; Sicre de Fontbrune, F.; Le Goff, J.; et al.
Abstract: Pre-emptive antiviral treatment efficiently prevents occurrence of cytomegalovirus (CMV) disease in allogeneic stem cell transplant recipients. However, successive treatment courses can be necessary. The current study was aimed at determining factors that could influence the response to antiviral treatment, in particular the donor CMV serostatus. A total of 147 consecutive CMV-seropositive recipients (R+) were included and prospectively monitored for 6 months after transplantation. Reactivation of CMV occurred in 111 patients, 61 of 78 with a CMV-positive donor (D+) and in 50 of 69 with a CMV-negative donor (D–) (p 0.45). Baseline viral loads and initial viral doubling times did not differ between D+/R+ and D–/R+. Fifteen D+/R+ and four D–/R+ had self-resolving CMV infections. A total of 92 patients received antiviral treatment and 81 (88%) had a significant decrease in CMV load under therapy. Repeated CMV episodes were observed in 67% of those and were significantly more frequent in D–/R+ than in D+/R+ (p <0001). Half-life of CMV under treatment was significantly longer in D–/R+ than in D+/R+. Treatment failure observed in eight recipients was associated with low leucocyte count at reactivation onset, and was significantly more frequent in D–/R+ (six patients) than in D+/R+ (two patients) (p <0.0001). CMV strains resistant to antivirals were found in two D–/R+. Donor CMV serostatus influenced neither CMV reactivation occurrence nor the kinetics of CMV DNA load in the early phase of CMV replication but had a significant impact on response to antiviral therapy. Virological drug-resistance remained rare.